Living well with a long-term health condition an evidence-based guide to managing your symptoms - Bogosian, Angeliki (Routledge, 2020)
Living well with along-term health conditionis one of the most challenging experiences one can have. Written based on the most recent research evidence, this straightforward guide to managing both the emotional and physical aspects of chronic illness gives practical suggestions of how those living with a range of conditions can most effectively manage their symptoms whilst still living an active and fulfilling life. Covering a range of topics including self-management of pain, fatigue, stress and lifestyle changes, and adapting to a diagnosis, the book provides an accessible resource that will enable patients and carers to better understand and meet the psychological challenges of long-term condition. By taking a holistic approach, Bogosian empowers the individual to identify their own goals and the pathways to achieve them to reach personal satisfaction, while negotiating the complexities of their condition. This book will be an indispensable guide to those living with a long-term illness, as well as their family members. It will also be of interest to specialist nurses, care consultants, or social workers working with people with a chronic illness